The Madinah Charter as the Basis of the Concept and Implementation of Civil Society - Yuniarto, Bambang; Afianti, Afi Nur; Masyhudi, Muhammad Rosyid; Kasih, Muizzar; Khodijah, Khodijah (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to understand the Medina charter as a basis for the concept and implementation of civil society. The basic premise of this research is that the Medina Charter was formed because the Prophet Muhammad wanted to bring social change to the people of Medina at that time. One example of the dynamics of social development in Yathrib (Medina) at that time was called structural change, namely change after change due to the processes of events that occurred in the form of increases in the number of adherents of Islam, the decline of hostility and civil war, so that the implication was that society had significant developments over the decades. per decade. Indonesia is a country whose social and cultural content is almost the same as Medina. If Indonesia is attributed to the Jakarta Charter which is implied in the 1945 Constitution as a legal role. The data collection method in this research uses a qualitative research method with a literature review as the approach, with heuristic, criticism, interpretation and historiography steps. The results of this research are that the Medina Charter was able to change the existence of every individual and human group from being just a collection of people to a political society, with the result of becoming a society that has sovereignty and political authority, thus forming a prosperous region and nation.